Chemical weathering records in Yungang Formation, North China: implications for stone heritage conservation - Huang, Xin; Guo, Feng; Zhao, Liang; Zhang, Feng (Frontiers in Earth Science, 2025)
The Yungang Grottoes located in Datong area, North China, have experienced extensive surface and structural damage. Previous studies have recognized the importance of temperature and water during weathering, but the quantitative evaluation on both the physical and chemical weathering remains absent. Here we conducted geochemical analyses on the sculpture-hosting sedimentary rocks of Shiku Member in Jurassic Yungang Formation. The results reveal that feldspar dissolution is predominant during chemical weathering, while the effects caused by other factors like calcic cement and sulphate are minor. The estimated chemical weathering rate of feldspar is 7.84 × 10−21 - 2.7 × 10−18 mol·cm-2·s−1, with an average cumulative chemical weathering amount of 1.46 × 10−11 mol·cm-2·y−1. The mass loss caused by chemical weathering is about 0.000061% per year and the annual mass loss rate is approximately 0.00015%–0.00018% when the effect of physical weathering is considered. The damage (5% mass loss) of Yungang Grottoes (450–520 AD) began in ca. AD 800 and all grottoes will be destroyed in the upcoming 4,000–5,000 years without protection. As the chemical weathering of feldspar is controlled by local temperature change, the grottoes should be accommodated in relatively constant low-temperature environment through adding eaves and air conditioners.